New therapeutic insights into radiation-induced myocardial fibrosis - Cheng-Xu Ma; Xin-Ke Zhao; Ying-Dong Li (Therapeutic Advances in Chronic Disease, 2019)
Radiation therapy (RT) for the treatment of thoracic tumors causes radiation-induced heart disease (RIHD). Radiation-induced myocardial fibrosis (RIMF) is both an acute and chronic stage of RIHD, depending on the specific pathology, and is thought to be a major risk factor for adverse myocardial remodeling and vascular changes. With the use of more three-dimensional conformal radiation regimens and early screenings and diagnoses for RIMF, the incidence of RIHD is declining, but it still must be carefully investigated to minimize the mortality and morbidity of patients with thoracic malignancies after RT treatment. Effective methods for preventing RIMF involve a decrease in the direct radiation dose in the heart, and early screening and diagnosis. Medications remain as a useful adjunct for preventing or treating RIMF. This review mainly discusses the cellular and molecular mechanisms underlying RIMF, and new therapeutic drugs that can potentially be developed from this knowledge.